Efektivitas Fraksi Ekstrak Daun Sirsak (Annona muricata L.) Terhadap Kadar Kolesterol Total - Akbar Awaluddin; A Zulkifli A S; Aswar Hasan; Nurzadrina Wahyuddin; Astuti Astuti (Jurnal Farmasi dan Ilmu Pengobatan, 2020)
Soursop leaves are reported to have several active compounds such as flavonoids, alkaloids and fatty acids and soursop leaves are reported to have many pharmacological effects, one of which is for the treatment of blood cholesterol levels. This study aims to compare the effectiveness of the active fraction of soursop (Annona muricata L.) ethanol extract on the reduction in total cholesterol levels of male mice (Mus musculus). The method used is to use 5 groups of male mice that were given 5 different treatments. Then proceed with a statistical test using LSD analysis. The results obtained showed that the effect of reducing total cholesterol of soursop leaf extract fraction at a dose of 100 mg/kg BB has no significant effect with positive control with a value of p = 0.501 > 0,05 and soursop leaf extract fraction dose of 150 mg/kgBB body weight with a value of p = 0.580 > 0.05. So, both are thought to be able to reduce total cholesterol levels which are almost the same as positive control.